The Influence of Product Quality and Location on the Purchase Decision in Bakso Damas Malang - Rahmadhani, Aisyah; Murtiyanto, Rizky Kurniawan (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
In today's globalized world, the culinary industry has seen remarkable growth, with product quality and strategic location being crucial factors. This study, titled "The Influence of Product Quality and Location on Purchase Decisions at Bakso Damas Malang," examines how these elements affect consumer choices, focusing on a prominent meatball vendor facing quality challenges despite a commitment to freshness. The urgency of this research stems from the rapid expansion and fierce competition in Malang's culinary sector. Quantitative analysis is essential to assess the impact of product quality and location on purchasing decisions. This research involves a substantial sample and employs a variety of data collection methods, including interviews, questionnaires, and observations, both online and offline. Validity and reliability tests ensure the robustness of the research tools, and a comprehensive analytical approach is used. The study finds that product quality and location significantly influence consumer decisions, with 71.8% of purchase decisions attributed to these factors, as indicated by the coefficient of determination (R2). The F-statistic test further confirms the combined effect of these variables. The study concludes that prioritizing product quality and strategic location is vital for businesses like Bakso Damas Malang to achieve sustained success and high consumer satisfaction.